PENGARUH PEMANFAATAN TEKNOLOGI, KOMPETENSI SUMBER DAYA MANUSIA DAN KOMITMEN ORGANISASI TERHADAP KUALITAS LAPORAN KEUANGAN SKPA PROVINSI ACEH - Pratama, Rian Rezky; Yahya, M. Rizal (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
The research examines the influence of The Use of Information Technology (PT), Human Resources Competence (SDM) and Organizational Commitment (KO) on the Quality of the financial statements (KLK). The population in this study is SKPA of Aceh Province. The sampling technique used is simple random sampling. This study uses primary data which obtained through the questionnaire results. The data were colleccted 63 questionnaires from 35 SKPA. Data were processed using SPSS version 22 and analyzed using multiple linear regression, F-Test, and t-test. The results show that simultaneously, The Use of Information Technology (PT), Human Resources Competence (SDM) and Organizational Commitment (KO) affect the Quality of the financial statements (KLK). Partially, each independent variable affect Quality of the financial statements.